SERUM ENZYMATIC AND ENDOCRINE PROFILE IN UTERINE TORSION AFFECTED BUFFALOES - PATELIYA, CHINTAN S; PATEL, J A; DHAMI, A J; MADHIRA, S P; SARVAIYA, N P (The Indian Journal of Animal Reproduction, 2023)
This study was conducted to investigate the endocrinal and enzymatic alterations in buffaloes suffering fromuterine torsion (Gr-I, n=10) in comparison to normal parturient buffaloes Gr-II, n=6) just before as well as 1 hr, 1 dayand 1 week after parturition. Serum enzymatic profile revealed that the mean values of serum AST and CPK weresignificantly higher in torsion affected buffaloes than normal parturient buffaloes at all peripartum intervals, whereas,the mean values of serum ALT were found significantly (p
Keywords: Uterine torsion; Buffaloes; ALT; AST; CPK; Cortisol; Estradiol; Progesterone